Challenges to legal theory : essays in honour of Professor José Iturmendi Morales - Iturmendi Morales, José; Falcón y Tella, María José; Martínez Muñoz, Juan Antonio; Jerry, Deirdre B. (Brill Nijhoff, 2021)
"Challenges to Legal Theory offers the reader a fascinating journey though a variety of multi-disciplinary topics, ranging from law and literature, and law and religion, to legal philosophy and constitutional law. The collection reflects some of the challenges that the field of legal theory currently faces. It is compiled by a selection of international and Spanish scholars, whose essays are made available in English translation for the first time. The volume is based on a collection of essays, published in Spanish, in honour of Professor José Iturmendi Morales, of Complutense University, Madrid, and brings the rich scholarship of pre-eminent Spanish scholars of law and legal theory to an international audience"--